The effectiveness of inquiry-based learning towards eleventh graders reading comprehension on analytical exposition text - Kristian Burhan; Yona Syaida Oktira; Helfany Amsa; Rahmat Debi (Geuthèë Institute, Aceh, 2023)
The purpose of this study was to determine the effectiveness of Inquiry-Based Learning on students' reading comprehension on analytical exposition text in the eleventh graders of MIPA of MAN 3 Pasaman Barat. The study was prompted by a number of issues that arise on a regular basis during the teaching and learning process, particularly in senior high school. The key issue that will be addressed in this study is the usage of teacher-centered learning, which prevents students from actively participating in the learning process. The experimental research was used in this study. The participants in this study were the eleventh graders of MIPA of MAN 3 Pasaman Barat. This study's sample consisted of 35 students from the XI MIPA 1 class as the experimental class and 35 students from the XI MIPA 2 class as the control class. According to the findings of this study, the mean score post-test experiment class was 68.15, whereas the control class was 64.07. As a result, the experimental class outperformed the control class. The reading ability of students was assessed using the t-test, which yielded Tcalculated = 2.13 and Ttable(0.95:62) = 1.676 at a 95% confidence level. It can be concluded that tcalculated > ttabel, as H0 was rejected and H1 was accepted. Thus, inquiry-based learning had a significant effect towards students' reading comprehension of analytical exposition text.